Elastomer-based MEMS optical interferometric transducers for highly sensitive surface stress sensing for biomolecular detection. (26th February 2019) - Takahashi, Kazuhiro; Fujie, Toshinori; Teramoto, Reina; Takahashi, Isao; Sato, Nobutaka; Takeoka, Shinji; Sawada, Kazuaki
Abstract: Abstract : We developed a microelectromechanical-system optical interferometer based on an elastomer nanosheet using a polystyrene-polybutadiene-polystyrene (SBS) triblock copolymer for a suspended membrane as a way to improve the stress sensitivity for surface stress detection. The elastomeric SBS nanosheet provides a low Young's modulus of 28 ± 11 MPa, a large elastic strain of 24 ± 12%, and high adhesiveness, of which the surface charge and mechanical property are tunable by layer-by-layer (LbL) deposition of polysaccharides. A freestanding SBS nanosheet can be formed above a microcavity using a dry transfer technique without applying vacuum or high-temperature processes. The maximum deflection associated with molecular adsorption increased by sevenfold compared with a parylene-C-based optical interferometric transducer.